Analysis of the therapeutic interaction provided by a humanoid robot serving stroke survivors as a therapeutic assistant for arm rehabilitation - Platz, Thomas; Pedersen, Ann Louise; Deutsch, Philipp; Umlauft, Alexandru-Nicolae; Bader, Sebastian (Frontiers in Robotics and AI, 2023)
Objective. To characterize a socially active humanoid robot’s therapeutic interaction as therapeutic assistant when providing arm rehabilitation (i.e. arm basis training, ABT for moderate to severe arm paresis or arm ability training, AAT for mild arm paresis) to stroke survivors when using the digital therapeutic system E-BRAiN (Evidence-Based Robot-Assistance in Neurorehabilitation). And, to compare it to human therapists’ interaction. Methods. Participants and therapy: Seventeen stroke survivors receiving arm rehabilitation (i.e. ABT [n=9] or AAT [n=8]) using E-BRAiN over a course of 9 sessions, and 21 other stroke survivors receiving arm rehabilitation sessions (i.e. ABT [n=6] or AAT [n=15]) in a conventional 1:1 therapist-patient setting. Analysis of therapeutic interaction: Therapy sessions were videotaped and all therapeutic interactions (information provision, feedback, and bond-related interaction) were documented offline both in terms of their frequency of occurrence and time used for the respective type of interaction using the instrument THER-I-ACT. Statistical analyses: Therapeutic interaction of the humanoid robot, supervising staff/therapists, and helpers on day 1 are reported as mean across subjects for each type of therapy (i.e. ABT and AAT, resp.) as descriptive statistics. Effects of time (day 1 vs. day 9) on humanoid robot interaction were analysed by repeated measures analysis of variance, rmANOVA together with the between subjects factor type of therapy (ABT vs. AAT). The between subjects effect of agent (humanoid robot vs. human therapist; day 1) was analysed together with the factor therapy (ABT vs. AAT) by ANOVA. Main results and interpretation. The overall pattern of therapeutic interaction by the humanoid robot was comprehensive and varied considerably with type of therapy (as clinically indicated and intended), largely comparable to human therapists’ interaction, and adapted according to needs for interaction over time. Even substantially long robot-assisted therapy sessions seemed acceptable to stroke survivors and promoted engaged patients’ training behaviour. Conclusion. Humanoid robot interaction as implemented in the digital system E-BRAiN matches human therapeutic interaction and its modification across therapies well and promotes engaged training behaviour by patients. These characteristics support its clinical use as therapeutic assistant and hence its application to support specific and intensive restaurative training for stroke survivors.